Anaesthetic complications of limb salvage surgeries : a 4 year retrospective study - Krisnan, Devanandhini (2006)
Objectives: Our purpose was to study the incidence of perioperative anaesthetic complications and morbidity following limb salvage surgeries as well as to determine the extent of contribution of preoperative status and duration of surgery towards incidences of these perioperative complications. Apart from that we aimed to study the extent and quality of postoperative care in limb salvage surgeries Study Design : The medical records of 120 patients who underwent limb salvage surgery were traced and studied for incidences of perioperative anaesthetic complications in 4 categories : hematological1 , temperature, cardiovascular and pulmonary. Necessary information were tabulated into individual data collection sheets (Appendix A). Results: There were no significant findings in the demographic data. Intraoperative hypothermia appeared to be the only significant perioperative anaesthetic complication. We were able to demonstrate a significant relationship between the duration of surgery I anaesthesia and the development of intraoperative hypothermia. Almost ~alf the patients were ventilated postoperatively whereby majority of care was instituted in the intensive care unit. Conclusion : Intraoperative hypothermia is an proven perioperative anaesthetic complication of limb salvage surgery. Incidences of hypothermia in limb salvage surgery are directly proportional to the duration of surgery and anaesthesia. Ventilation in the intensive care unit appears to be the most common postoperative care.